A COMPARATIVE ASSESSMENT OF FRAUD RELATED AUDITING STANDARDS: SA 316 VERSUS ISA 240 - Muhammad Fajar Ismail; Yeney W. Prihatiningtyas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of this study is to describe fraud related auditing standards that applicable in Indonesia, SA 316, and fraud related auditing standards that applicable worldwide, ISA 240. Understanding the similarities and differences of these standards are important for accountants or candidate of accountants who may be assigned to carry out the job related to fraud in various countries. This study is a descriptive one. The findings show that although both standards have similarities almost in all aspects of the main themes, the presentations are slightly different, particularly in term of “the tone of the language” (the rhetoric). The rhetoric used by ISA 240 are more straight forward, assertive, and clear than that of SA 316. ISA 240 explicitly emphasized in one of the sub themes about the urgency of professional skepticism, while SA 316 revealed it in a discussion on different sub themes, but both standards are emphasized the importance of professional skepticism. ISA 240 unequivocally stressed the importance of discussion among team members before and during the audit process; whilst SA 316 did not explicitly and clearly stated similar things. Finally, ISA 240 stressed the importance of management to carry out its role in the prevention and detection of fraud, while the SA 316 did not clearly state it. Keywords: fraud, auditing standard, SA 316, ISA 240